Fast Pyrolysis of Tropical Biomass Species and Influence of Water Pretreatment on Product Distributions. - Trevor James Morgan; Scott Q Turn; Ning Sun; Anthe George (PLoS ONE)
The fast pyrolysis behaviour of pretreated banagrass was examined at four temperatures (between 400 and 600 C) and four residence times (between ~1.2 and 12 s). The pretreatment used water washing/leaching to reduce the inorganic content of the banagrass. Yields of bio-oil, permanent gases and char were determined at each reaction condition and compared to previously published results from untreated banagrass. Comparing the bio-oil yields from the untreated and pretreated banagrass shows that the yields were greater from the pretreated banagrass by 4 to 11 wt% (absolute) at all reaction conditions. The effect of pretreatment (i.e. reducing the amount of ash, and alkali and alkali earth metals) on pyrolysis products is: 1) to increase the dry bio-oil yield, 2) to decrease the amount of undetected material, 3) to produce a slight increase in CO yield or no change, 4) to slightly decrease CO2 yield or no change, and 5) to produce a more stable bio-oil (less aging). Char yield and total gas yield were unaffected by feedstock pretreatment. Four other tropical biomass species were also pyrolyzed under one condition (450°C and 1.4 s residence time) for comparison to the banagrass results. The samples include two hardwoods: leucaena and eucalyptus, and two grasses: sugarcane bagasse and energy-cane. A sample of pretreated energy-cane was also pyrolyzed. Of the materials tested, the best feedstocks for fast pyrolysis were sugarcane bagasse, pretreated energy cane and eucalyptus based on the yields of 'dry bio-oil', CO and CO2. On the same basis, the least productive feedstocks are untreated banagrass followed by pretreated banagrass and leucaena.